THE INFLUENCE OF THE OUTCOME-BASED EDUCATION ON STUDENTS’ EMPLOYMENT INTENTION IN HIGHER EDUCATIONAL INSTITUTIONS IN GUANGDONG PROVINCE, CHINA - Wu, Jun; Senarith , Prapatpong; Moonmuang, Sukhum (วารสารวิจัยธรรมศึกษา, 2022)
The objectives of this research were: To the influence of Outcome-Based Education on students’ employment intention; and to the interplay of cognition, attitude and motivation as mediating variables between Outcome-Based Education and students’ employment intention. The research was a mixed methodology research. Population was the 4th-year students studying in universities in Guangdong Province in 2021 are the research object, totalling 100,000. The sample size was determined by Optimal Design plus Empirical Evidence, obtained by of the research adopts polymorphic random sampling method, totalling 511, obtained by purposive sampling method. The instruments used for data collection was a questionnaire which composed of six parts (five-level rating scale). The statistics used for data analysis were IBM SPSS Statistics and Amos Graphics. The research findings revealed that; (1) There were some positive relationships between Outcome-Based Education and student’s employment intention; and (2) There were some positive relationships between cognitive and student’s employment intention; and (3) There was no relationship between attitude and student’s employment intention; and (4) There were some positive relationships between motivation and student’s employment intention; and (5) There were some positive relationships between cognitive and student’s motivation; and (6) There were some positive relationships between attitude and student’s motivation; and (7) There were some positive relationships between Outcome-Based Education and student’s cognitive; and (8) There were some positive relationships between attitude and student’s cognitive; and (9) There were some positive relationships between cognitive and student’s attitude; and (10) There were some positive relationships between Outcome-Based Education and student’s attitude.